Layered sheet, building material, and communication equipment enclosure
The laminated sheet with a concave-convex structure and alternating laminate units addresses the challenges of moldability, strength, and wide-frequency electromagnetic wave absorption, achieving high return loss and effective shielding across a broad frequency range.
Patent Information
- Application Number
- JP2023150717
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-19
- Publication Date
- 2025-04-01
AI Technical Summary
Existing electromagnetic wave shielding materials face challenges in terms of moldability, strength, and effective absorption of electromagnetic waves across a wide frequency range, particularly in the GHz band.
A laminated sheet with a concave-convex structure, featuring alternating laminate units of two different types of layers (Layer A and Layer B) stacked in total, which provides excellent moldability, strength, and electromagnetic wave absorption capabilities.
The laminated sheet achieves high electromagnetic wave absorption with a return loss of 5.0 dB or more across a wide frequency range of 1GHz to 1000GHz, ensuring effective shielding and moldability suitable for various applications.
Smart Images

Figure 2025043446000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate sheet having excellent moldability, strength and electromagnetic wave absorption properties, and to a building material or a communication device housing using the same. [Background technology]
[0002] With advances in communication technology, in recent years, meter waves in the hundreds of MHz to several GHz band are mainly used for mobile phones, wireless communications, etc. More specifically, centimeter waves in the several GHz to several tens of GHz band are mainly used for mobile communications such as 4G and 5G and wireless LAN (Wi-fi) communications, while millimeter waves in the tens of GHz to several hundreds of GHz band are mainly used for automobile collision prevention radar, etc.
[0003] Thus, the frequency band of electromagnetic waves is selected according to the capacity of information, the distance to be transmitted, and the purpose of use. However, since electromagnetic waves of similar frequency bands are used in various devices and applications, there are concerns about malfunction of devices, communication failure, information leakage, etc. In addition, the effects of electromagnetic waves on the human body, which is sensitive to electromagnetic waves, have also been pointed out. In response to these concerns and points, there is an increasing need for electromagnetic wave shielding materials that block electromagnetic waves. In particular, in recent years, the development of communication technologies that use electromagnetic waves in the GHz frequency band has accelerated in order to realize high-speed, large-capacity communication, and there is a demand for electromagnetic wave shielding materials that can block electromagnetic waves in this frequency band.
[0004] Electromagnetic waves propagate through space as waves made up of two components: an electric field and a magnetic field. Electromagnetic shielding materials that block electromagnetic waves can reflect electromagnetic waves on their surface or inside, or absorb them inside the material, causing the loss and attenuation of the energy of the electromagnetic waves. Combining reflection and absorption can increase the effect even more.
[0005] For example, conductive reflection technology that uses reflection on the surface of an electromagnetic shielding material can be more effective when the electrical resistance (impedance calculated based on the dielectric constant) of the air interface and the interface of the electromagnetic shielding material is different. Generally, high electromagnetic shielding properties can be achieved over a wide range of frequency bands by coating and laminating a material with a very low resistance, such as metal (copper), onto the surface of the base material (Patent Document 1).
[0006] On the other hand, electromagnetic wave absorption technology that uses absorption within the electromagnetic wave shielding material involves incorporating conductive and / or magnetic materials into the material, converting the electromagnetic waves that enter the material into induced current, thereby dissipating the energy of the electromagnetic waves, and absorption performance can be achieved by incorporating metal materials such as carbon materials and ferrite into dielectric polymers such as rubber (Patent Documents 2 to 4). In addition, by overlapping layers with different impedances, electromagnetic waves reflected on the front and back of the electromagnetic wave shielding material can be interfered with and canceled out, resulting in loss (Patent Document 5).
[0007] In particular, the electromagnetic wave shielding properties due to absorption vary depending on the combination of the dielectric (insulating) substrate and the conductive material contained therein, the substrate thickness, the formulation of the conductive material (type of material, combination method, content), etc., but the arrangement state of the conductive material within the substrate is also an important factor. For example, there is a finding called the Maxwell-Wagner effect, which shows that the effect of the entire shielding material can be improved by arranging conductive materials in a certain direction and overlapping them side by side to improve conductivity (Non-Patent Document 1). As an electromagnetic wave absorbing material utilizing the Maxwell-Wagner effect, a film in which low dielectric layers and high dielectric layers are alternately laminated has been disclosed (Patent Document 6). [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Special Publication No. 2011-502285 [Patent Document 2] JP 2003-158395 A [Patent Document 3] JP 2017-118073 A [Patent Document 4] JP 2019-057730 A [Patent Document 5] JP 2019-102665 A [Patent Document 6] International Publication No. 2021 / 100566 [Non-patent literature]
[0009] [Non-Patent Document 1] ZMDang,Prog.Matter.Sci.,2012,57,660-723 Summary of the Invention [Problem to be solved by the invention]
[0010] However, in electromagnetic shielding materials that utilize conductive reflection technology due to reflection on the surface of the electromagnetic shielding material as described in Patent Document 1, metal sputtering, vacuum deposition, or a technology of coating the outermost layer with a paste material containing a conductive and / or magnetic material is used, but problems may arise in terms of peeling off, causing short circuits in electronic devices or communication devices, or reduced durability and strength.
[0011] On the other hand, in the case of electromagnetic shielding materials using electromagnetic wave absorption technology by internal absorption as described in Patent Documents 2 to 5, in the existing technology in which a conductive material is contained in the substrate, in order to increase the absolute value of the electromagnetic wave attenuation (to increase the electromagnetic wave shielding property), it was necessary to thicken the substrate or increase the content of the conductive material. In other words, in such electromagnetic shielding materials, once the material to be used is determined, the electromagnetic wave shielding property is determined in proportion to the product of the amount of conductive material contained per unit volume of the substrate and the thickness of the substrate (such a relationship is called the "volume law"). However, when the thickness of the substrate is increased, the stiffness of the electromagnetic shielding material increases, making it difficult to apply the material to applications requiring formability, such as wrapping the material around a cable or combining the electromagnetic shielding material along a housing having a complex uneven shape.
[0012] In addition, when considering the moldability and production efficiency of electromagnetic wave shielding materials, continuous sheeting by melt extrusion using thermoplastic resin is preferable to press-processed products using thermoplastic resin, but when forming a sheet containing a high concentration of conductive material, the thickening effect (thixotropy) of the resin composition during extrusion becomes strong, causing uneven extrusion when extruding into a sheet. Therefore, there were issues such as the difficulty of forming a sheet of uniform thickness and the sheet becoming brittle and prone to cracking.
[0013] According to the method of Patent Document 6, a sheet with electromagnetic wave absorbing properties can be obtained by melt extrusion, but when actually used around communication devices, there are cases where absorption characteristics over a sufficient range cannot be obtained. This is because the frequency at which electromagnetic waves are absorbed is pinpointed, so when electromagnetic waves come from an oblique angle, the absorbing frequency shifts, and sufficient absorption performance cannot be achieved.
[0014] The present invention has an object to solve the above problems and to provide a sheet having excellent moldability and strength and electromagnetic wave absorbing properties capable of absorbing waves up to the high frequency band. [Means for solving the problem]
[0015] In order to solve the above problems, the present invention has the following configuration: A laminate sheet characterized in that the return loss at the maximum peak in a return loss curve in a frequency band of 1 GHz to 1000 GHz is 5.0 dB or more, the laminate sheet includes an alternating laminate unit in which two different types of layers (layers A and layers B) are alternately laminated in a total of five or more layers, and the laminate sheet has a concave-convex structure.
[0016] The laminate sheet of the present invention can also be formed into the following embodiments, and can also be used to make a housing for a communication device or a building material. (1) A laminated sheet, characterized in that the return loss at the maximum peak in a return loss curve in the frequency band of 1 GHz to 1000 GHz is 5.0 dB or more, the sheet includes an alternating laminate unit in which two different types of layers (layers A and layers B) are alternately laminated to a total of five or more layers, and the laminate has an uneven structure. (2) The laminate sheet according to (1), wherein when a structure in which a convex portion is surrounded by a concave portion is defined as Structure X and a structure in which a concave portion is surrounded by a convex portion is defined as Structure Y, the concave-convex structure has at least one of Structure X and Structure Y. (3) A laminate sheet according to claim (2), having at least one of the following characteristics 1 and 2. Feature 1: In the structure X, the distance between the centers of the most adjacent convex portions (pitch X) is constant. Feature 2: The distance (pitch Y) between the centers of the most adjacent recesses in the structure Y is constant. (4) The laminate sheet according to (3), wherein at least one of the pitch X and the pitch Y is 0.6 mm or more and 30 cm or less. (5) The laminate sheet according to (3) or (4), which has at least one of the following characteristics 3 and 4: Feature 3: The average width of the recesses in the structure X is 5% or more and 20% or less of the pitch X. Feature 4: The average width of the convex portions in the structure Y is 5% or more and 20% or less of the pitch Y. (6) The laminate sheet according to any one of (3) to (5), which has at least one of the following characteristics 5 and 6: Feature 5: The depth of the recess in the structure X is 70% or less of the sheet thickness and 1% or more of the pitch X. Feature 6: The height of the convex portion in the structure Y is 70% or less of the sheet thickness and 1% or more of the pitch Y. (7) The laminate sheet according to any one of (2) to (6), which has at least one of the following characteristics 7 and 8: Feature 7: The average value of the thickness of each layer of the alternating laminate unit is 1% to 40% of the depth of the recess in the structure X. Feature 8: The average value of the thickness of each layer of the alternating laminate unit is 1% to 40% of the height of the protrusions in the structure Y. (8) The laminate sheet according to any one of (3) to (7), which has at least one of the following features 9 and 10: Feature 9: When the length of the pitch X is continuously evaluated at 50 points in the same direction, the standard deviation is 10% or less of the average value. Feature 10: When the length of the pitch Y is evaluated at 50 consecutive points in the same direction, the standard deviation is 10% or less of the average value. (9) The laminate sheet according to any one of (1) to (8), wherein the thickness of at least one outermost layer is 5% to 40% of the entire sheet. (10) The laminate sheet according to any one of (1) to (9), wherein the maximum value of Young's modulus at 80° C. is 50 MPa or more and 200 MPa or less. (11) The laminate sheet according to any one of (1) to (10), having a minimum Young's modulus at 25° C. of 800 MPa or more. (12) The laminate sheet according to any one of (1) to (11), which has a visible light transmittance of 10% or less. (13) The laminate sheet according to any one of (1) to (12), wherein the frequency bandwidth in which the return loss is 5.0 dB or more at the maximum peak is 1.0 GHz or more and 100 GHz or less. (14) The laminate sheet according to any one of (1) to (13), wherein the frequency bandwidth in which the return loss is 20 dB or more at the maximum peak is 1.0 GHz or more and 100 GHz or less. (15) A building material having the laminate sheet according to any one of (1) to (14). (16) A housing for a communication device, comprising the laminate sheet according to any one of (1) to (14). (17) A housing for a communication device as described in (16), which has a laminate sheet as described in any one of (1) to (14) in a direction opposite to the transmission or reception direction of at least one of a receiving antenna, a transmitting antenna, or a transmitting / receiving antenna, and the distance between the laminate sheet and the antenna is 1 to 1,000 times the wavelength of the electromagnetic wave to be transmitted or received. (18) The housing for a communication device according to (16) or (17), wherein the polarization direction of the main lobe of the antenna and the direction of strong electromagnetic wave absorption of the laminate sheet are perpendicular to each other. Effect of the Invention
[0017] According to the present invention, it is possible to provide a laminate sheet that is excellent in formability, strength, and electromagnetic wave absorption properties, and is capable of absorbing electromagnetic waves over a wide frequency range due to its uneven structure. Since the laminate sheet of the present invention has the above properties, it can be suitably used as a building material or a housing for communication devices. [Brief description of the drawings]
[0018] [Figure 1] FIG. 2 is a schematic diagram showing an example of a concave-convex structure not having structures X and Y. [Diagram 2] FIG. 2 is a schematic diagram showing an example of a concavo-convex structure having a structure Y (random). [Diagram 3] FIG. 2 is a schematic diagram showing an example of a concavo-convex structure having a structure X (random). [Figure 4] FIG. 2 is a schematic diagram showing an example of a concavo-convex structure having a structure Y (periodic). [Diagram 5] FIG. 2 is a schematic diagram showing an example of a concave-convex structure having a structure X (periodic). [Figure 6] FIG. 13 is a schematic diagram showing a metal housing for evaluating communication strength. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The laminated sheet of the present invention will be described in detail below. The laminated sheet of the present invention is characterized in that it has a return loss of 5.0 dB or more at the maximum peak in a return loss curve in a frequency band of 1 GHz to 1000 GHz, includes an alternating laminate unit in which two different types of layers (layers A and B) are alternately laminated for a total of five or more layers, and has a concave-convex structure. Note that hereinafter, "the maximum peak in a return loss curve in a frequency band of 1 GHz to 1000 GHz" may be simply referred to as "maximum peak".
[0020] The laminate sheet of the present invention has a return loss of 5.0 dB or more at the maximum peak in the return loss curve in the frequency band of 1 GHz to 1000 GHz. Here, a return loss of less than 5.0 dB means that the electromagnetic wave transmittance is higher than 30%. Therefore, a laminate sheet having a return loss of less than 5.0 dB at the maximum peak cannot be said to have sufficient electromagnetic wave absorption properties.
[0021] From the viewpoint of ensuring sufficient electromagnetic wave absorption, the return loss of the maximum peak in the laminated sheet of the present invention is preferably 15.0 dB or more, more preferably 17.0 dB or more, even more preferably 20.0 dB or more, particularly preferably 23.0 dB or more, and most preferably 26.0 dB or more. When the return loss at the maximum peak is about 30.0 dB, 99.9% of the incident electromagnetic wave is shielded, and the laminated sheet can be said to have very high electromagnetic wave absorption. From the above viewpoint, the return loss at the maximum peak is preferably as large as possible, and the upper limit is not particularly limited, but from the viewpoint of feasibility, it is preferably 100 dB, more preferably 35.0 dB.
[0022] In the laminated film of the present invention, it is preferable that the frequency bandwidth in which the return loss is 5.0 dB or more at the maximum peak is 1.0 GHz or more and 100 GHz or less, and the frequency bandwidth in which the return loss is 20 dB or more at the maximum peak is 1.0 GHz or more and 20 GHz or less. When the frequency bandwidth in which the return loss at the maximum peak is 5.0 dB or more or 20 dB or more is wide, not only can a steep and high electromagnetic wave absorption be realized, but also the fluctuation of the frequency band due to the uneven thickness of the laminated sheet and the change in the absorption frequency due to the incidence angle of the electromagnetic wave can be reduced. In addition, in such an embodiment, the influence of the fluctuation of the reflected frequency band due to the shape change due to molding or the like can be suppressed, so that when used for, for example, millimeter wave radar applications, the effects of suppressing false detection, improving communication strength, improving communication stability, etc. can be enhanced. From the above viewpoint, it is more preferable to satisfy both of these.
[0023] From the above viewpoint, the frequency bandwidth in which the return loss at the maximum peak is 5.0 dB or more is preferably 1.0 GHz or more, more preferably 10 GHz or more, even more preferably 20 GHz or more, and particularly preferably 23 GHz or more. From the viewpoint of feasibility, the upper limit is preferably 100 GHz, more preferably 80 GHz, and even more preferably 40 GHz.
[0024] From the above viewpoint, the frequency bandwidth in which the return loss at the maximum peak is 20 dB or more is preferably 1.0 GHz or more, more preferably 3.0 GHz or more, further preferably 4.0 GHz or more, and particularly preferably 6.0 GHz or more. From the viewpoint of feasibility, the upper limit is preferably 20 GHz, and more preferably 10 GHz.
[0025] The frequency bandwidth in which the return loss is 5.0 dB or more can be broadened by forming, for example, a concave-convex structure, preferably a concave-convex structure having structure X or structure Y, as described below. Furthermore, the depth and height of the concave-convex structure may be adjusted as described below. This is because the thickness of the laminated sheet and the thickness of each layer constituting the alternating laminated unit are not constant due to the concave-convex structure of the laminated sheet, making it possible to provide a width in the frequency to be absorbed. In addition, since the number of layers constituting the alternating laminated unit increases, the number of layer interfaces also increases, and interference reflection is strengthened, it is also effective to increase the number of layers. In addition, it is also effective to add a metal material with a high aspect ratio to the laminated sheet to realize the arrangement of the metal material in the surface direction. These methods can be used in combination as appropriate, and can also be used as a method for setting the frequency bandwidth in which the return loss is 20 dB or more at the maximum peak to 1.0 GHz or more and 20 GHz or less.
[0026] When the laminated sheet of the present invention is used for absorbing electromagnetic waves, it is necessary to absorb the GHz frequency band, so it is preferable that the laminated sheet has a maximum peak in that region. In general, in order to absorb the near-field, which corresponds to a frequency band of less than several GHz, a sheet is used in which a magnetic material such as a metal represented by silver or copper or a metal oxide such as ferrite is contained in a dielectric substrate.
[0027] When aiming for shielding of high frequencies in the GHz range, magnetic materials have a characteristic (Snoek limit) that makes it impossible to obtain magnetic loss above a certain frequency, so the laminated sheet is usually covered by including a high concentration of magnetic material. On the other hand, when producing a laminated sheet by melt extrusion, thixotropy is unavoidable due to the high concentration of filler as a magnetic material, and the added magnetic material may cause damage to the embossed metal part of the extruder. Therefore, it is preferable to produce a laminated sheet by the melt extrusion process while keeping the filler concentration low.
[0028] When preparing a laminated sheet by melt extrusion while keeping the filler concentration low, in order to obtain a laminated sheet having electromagnetic shielding properties in the above-mentioned GHz frequency band, it is preferable to increase the electromagnetic wave absorption in the high frequency band by absorbing electromagnetic waves by adding a certain level or more of a conductive material or a conductive / magnetic composite material. When targeting a frequency band of several GHz by using a magnetic material in combination, it is preferable to use a metal material with a high aspect ratio that can achieve loss due to high magnetic permeability. By adding a metal material with a high aspect ratio to the laminated sheet, it is possible to realize the arrangement of the material in the plane direction, which is difficult to achieve with a conventional single film, and a laminated sheet that exhibits absorption properties even in the GHz frequency band can be obtained.
[0029] The aspect ratio can be expressed as the ratio of the length in the thickness direction of the material to the length of the major axis in the planar direction, and if the former is t1 and the latter is t2, then t1 / t2 is preferably 0.001 to 0.95, more preferably 0.01 to 0.10. If the aspect ratio is made larger than 0.001, the magnetic material will not become too thin, and deformation and damage of the magnetic material during the compounding and film-forming processes will be suppressed, reducing loss of effectiveness of the magnetic material.
[0030] The method of identifying the maximum peak in the return loss curve in the frequency band of 1 GHz to 1000 GHz, the method of measuring the return loss at the maximum peak, and the method of identifying the frequency bandwidth in which the return loss is 5.0 dB or more and 20 dB or more will be described later. In summary, as a method of obtaining a laminated sheet in which the return loss at the maximum peak is 5.0 dB or more, for example, it is effective to include a certain level or more of a conductive material or a conductive / magnetic composite material, to include a spherical magnetic material and a metal material with a high aspect ratio, or to form a concave-convex structure, preferably a concave-convex structure having a structure X or structure Y, as described later.
[0031] The laminated sheet of the present invention includes an alternating laminate unit in which two different layers (layers A and B) are alternately laminated for a total of five or more layers. Here, "different from each other" refers to the fact that at least one of the resin and particles constituting each layer has a different composition, which can be confirmed by the following method.
[0032] Specifically, when at least one of the following (1) to (5) is satisfied, the layers can be considered to have different compositions. (1): The elastic modulus of the film cross section is evaluated by dynamic viscoelastic measurement using an atomic force microscope (AFM-DMA), and the ratio of the average elastic modulus of the two layers is 1.1 or more. (2): The surface potential is evaluated using an electric force microscope (EFM), and the ratio of the average surface potentials of the two layers is 1.1 or greater. (3): The concentration of each atom is evaluated using energy dispersive X-ray spectroscopy (SEM-EDX), and the ratio of the mole fraction (or weight fraction) of each atom in the two layers is 1.1 or more. (4) The two layers can be peeled off, and the density, glass transition temperature, melting point, decomposition temperature, and ash content after decomposition are evaluated between the two layers, and at least one of the values differs by 3° C. or more, or 10% or more. In the present invention, the melting point and glass transition temperature can be measured by the method described in JIS K-7122 (1987) (the details of the measurement method will be described later). (5) When the cross section is observed at the desired magnification (500 to 20,000 times) with a transmission electron microscope (TEM) or scanning electron microscope (SEM), the interface can be confirmed. (In this case, "the interface can be confirmed" means that the brightness between adjacent layers is different. Specifically, first, the brightness is measured at 1,000 points for each layer. Next, the average brightness for each layer and the standard deviation for the brightness for each layer are calculated. If the difference in the average brightness of two adjacent layers is greater than the standard deviation of the brightness of each of the two layers, the brightness is deemed to be different.)
[0033] Which of the two types of layers is to be layer A and which is to be layer B can be determined by determining which has a higher surface potential in EFM as layer B. When conductive particles, dielectric materials, or magnetic particles are added to layer B to adjust the dielectric constant, it is preferable to make layer A the outermost layer from the viewpoints of film formability and prevention of particle shedding.
[0034] The resins used in the layers A and B of the laminate sheet of the present invention are preferably thermoplastic resins, from the viewpoint of improving the processability and film-forming properties of the sheet.Examples of thermoplastic resins include polyolefin resins such as polyethylene, polypropylene, poly(1-butene), poly(4-methylpentene), polyisobutylene, polyisoprene, polybutadiene, polyvinylcyclohexane, polystyrene, poly(α-methylstyrene), poly(p-methylstyrene), polynorbornene, and polycyclopentene; polyamide resins such as nylon 6, nylon 11, nylon 12, and nylon 66; copolymer resins of vinyl monomers such as ethylene / propylene copolymer, ethylene / vinylcyclohexane copolymer, ethylene / vinylcyclohexene copolymer, ethylene / alkylacrylate copolymer, ethylene / acrylic methacrylate copolymer, ethylene / norbornene copolymer, ethylene / vinyl acetate copolymer, propylene / butadiene copolymer, isobutylene / isoprene copolymer, and vinyl chloride / vinyl acetate copolymer; acrylic resins such as polyacrylate, polymethacrylate, polymethyl methacrylate, polyacrylamide, and polyacrylonitrile; Polyester resins such as polyethylene terephthalate, polypropylene terephthalate, polybutylene terephthalate, and polyethylene-2,6-naphthalate; polyether resins such as polyethylene oxide, polypropylene oxide, and polyacrylene glycol; cellulose ester resins such as diacetyl cellulose, triacetyl cellulose, propionyl cellulose, butyryl cellulose, acetylpropionyl cellulose, and nitrocellulose; biodegradable polymers such as polylactic acid and polybutyl succinate; and other polymers such as polyvinyl chloride, polyvinylidene chloride, polyvinyl alcohol, polyvinyl butyral, polyacetal, polyglycolic acid, polycarbonate, polyketone, polyether sulfone, polyether ether ketone, modified polyphenylene ether, polyphenylene sulfide, polyetherimide, polyimide, polysiloxane, tetrafluoroethylene resin, trifluoroethylene resin, trichloroethylene resin, tetrafluoroethylene-hexafluoropropylene copolymer, and polyvinylidene fluoride can be used.As long as the effects of the present invention are not impaired, these resins may be used alone or in combination in each layer.
[0035] The laminated sheet of the present invention preferably contains a conductive material (dielectric particles or conductive particles) to enhance the electromagnetic wave absorption performance. Examples of the conductive material include particles with anisotropic dielectric constant such as titanium oxide and barium titanate, carbon nanotubes such as single-walled nanotubes, multi-walled nanotubes, and cup-stacked nanotubes, which are cylindrical carbons, and conductive particles with anisotropic shape such as flat carbons such as graphite, graphite, and graphene, cylindrical graphite, carbon microcoils, fullerenes, carbon fibers (long fibers, short fibers), needle-shaped titanium oxide, and plate-shaped titanium oxide, and conductive particles with small anisotropy such as carbon black (spherical carbon) and spherical graphite such as acetylene black, channel black, lamp black, thermal black, ketjen black, and furnace black. These conductive materials may be used alone or in combination of multiple types.
[0036] By laminating five or more layers of two different types of layers alternately, the layer with excellent formability acts as a support layer, improving strength and preventing defects such as tears and holes during molding. In addition, thermally crystallized sheets generally become brittle, but in the present invention, each layer is made thin, preventing thermal crystallization, and therefore preventing defects such as cracks during molding.
[0037] Furthermore, while the resin is subjected to large deformation during molding, it is desirable that the resin is resistant to impacts and scratches (small deformations) after molding, and also that the resin has a degree of conformability that allows it to be used in molding components of various shapes. By having a laminated structure such as the laminated sheet of the present invention, the interface layers between the layers of the laminated sheet maintain their shape against small deformations, but against large deformations, minute fractures and slippage at the interface are caused. Therefore, by multi-layering, the resistance to small deformations is increased, and at the same time, good formability is obtained, resulting in a laminated sheet that can sufficiently conform to recessed parts that are relatively difficult to mold.
[0038] From the above viewpoints, the total number of layers in the alternating laminate unit in which two different types of layers (layers A and B) are alternately laminated is preferably 11 or more, more preferably 51 or more, and particularly preferably 201 or more. There is no particular upper limit to the number of layers in the alternating unit, but from the viewpoint of film formation stability, the maximum is about 2001 layers.
[0039] The laminated sheet of the present invention has an uneven structure from the viewpoint of providing a range of frequencies to be absorbed. When the laminated sheet has an uneven structure, the thickness of the laminated sheet is not constant, so that it is possible to provide a range of frequencies to be absorbed. Therefore, for example, even when electromagnetic waves are incident from an oblique direction rather than perpendicular to the laminated sheet surface, the laminated sheet can absorb electromagnetic waves in a desired band. Here, the uneven structure refers to a structure having unevenness with a surface roughness (Ra) of 1.5 μm or more. The method of measuring the surface roughness is based on the height of the unevenness of the surface, and if it is 0.1 mm or less, a three-dimensional roughness meter can be used, and if it is more than 0.1 mm, a 3D shape measuring machine can be used (details of the measurement method will be described later).
[0040] In the laminated film of the present invention, when a structure in which a convex portion is surrounded by a concave portion is structure X, and a structure in which a concave portion is surrounded by a convex portion is structure Y, it is preferable that the concave-convex structure has at least one of structure X and structure Y. Here, the concave portion refers to a portion lower than the average height of the sheet surface, and the convex portion refers to a portion higher than the average height of the sheet surface. Even in the case of a structure in which convex portions and concave portions are continuous (FIG. 1), in other words, a structure having a concave-convex structure but not having structure X or structure Y, the effect of providing a width to the frequency to be absorbed can be obtained. On the other hand, in the case of an embodiment having a concave-convex structure but not having structure X or structure Y, when a force is applied, the force is concentrated on the concave portion, making it easy to break, and there are cases where the strength is inferior. In addition, in such an embodiment, anisotropy occurs, and therefore the absorption characteristics differ depending on the polarization of the electromagnetic wave, and stable performance may not be obtained. By adopting an embodiment having structure X or Y, these problems can also be solved. In FIG. 1, reference numeral 1 represents a concave portion, and reference numeral 2 represents a convex portion (the same applies to FIGS. 2 to 5 described later).
[0041] Examples of the structure having Structure X or Y include a structure having randomly arranged concave portions surrounded by convex portions as shown in FIG. 2, a structure having randomly arranged convex portions surrounded by concave portions as shown in FIG. 3, a structure having a periodic pattern of concave portions surrounded by convex portions as shown in FIG. 4, and a structure having a periodic pattern of convex portions surrounded by concave portions as shown in FIG. 5.
[0042] Particularly preferred is a structure in which the convex or concave portions are arranged periodically (for example, the structure exemplified in FIG. 4 or FIG. 5). The periodic arrangement of the concave or convex portions can broaden the absorption band compared to the case in which they are arranged randomly. Periodic arrangement here refers to the fact that, among independent convex portions / concave portions, the distance between the centers of adjacent convex portions / concave portions (pitch X / pitch Y) is constant. In other words, it is preferable that the laminated sheet of the present invention has at least one of the following features 1 and 2. Feature 1: In the structure X, the distance between the centers of the most adjacent convex portions (pitch X) is constant. Feature 2: The distance (pitch Y) between the centers of the most adjacent recesses in the structure Y is constant.
[0043] Here, pitch X refers to the distance between the centers of the closest protrusions, and pitch Y refers to the distance between the centers of the closest recesses. In the case of a double doughnut shape, where one protrusion / recess exists inside another protrusion / recess, pitch Y refers to the distance between the centers of the closest protrusions / recesses excluding the area surrounded by the protrusions / recesses.
[0044] As a method for forming the above-mentioned uneven structure, any method such as embossing, brushing, imprinting, vacuum pressure molding, laser ablation, blasting, etc. can be used. Among them, embossing, imprinting, and vacuum pressure molding are preferable because they can easily form a periodic structure. In these processing methods, the processing temperature is preferably set within the range of glass transition temperature to glass transition temperature + 100°C and below the melting point for all thermoplastic resins constituting the sheet (however, the temperature condition of "below the melting point" does not need to be considered for thermoplastic resins that do not have a melting point). In addition, in the embossing process, it is also preferable to apply a release agent to at least one of the embossing roll and the mold to improve the releasability of the sheet and suppress the change in the shape of the uneven structure when peeled off.
[0045] In the laminated sheet of the present invention, at least one of the pitch X and the pitch Y is preferably 0.6 mm or more and 30 cm or less. By setting the pitch X and the pitch Y in this range, it is possible to strongly absorb electromagnetic waves of a frequency corresponding to the pitch X and the pitch Y. From the above viewpoint, it is preferably 5 mm or more and 100 mm or less, and more preferably 7 mm or more and 50 mm or less. The size of the pitch X and the pitch Y can be controlled by the shape of the embossing roll, the shape of the imprinting mold, and the shape of the vacuum pressure molding mold. The size of the pitch X and the pitch Y can be measured by observing the thickness direction cross section (cross section perpendicular to the sheet surface) with a digital microscope and measuring it with its length measuring function, or by measuring it with a length measuring instrument such as a ruler, and the details will be described later.
[0046] From the viewpoints of electromagnetic wave absorbing performance, productivity, and the like, the laminate sheet of the present invention preferably has at least one of the following features 3 and 4. Feature 3: The average width of the recesses in structure X is 5% or more and 20% or less of pitch X. Feature 4: The average width of the convex portions in structure Y is 5% or more and 20% or less of pitch Y.
[0047] Here, the width of the recesses in Structure X refers to the average value of the length of the recesses on a straight line with pitch X, and the width of the protrusions in Structure Y refers to the average value of the length of the protrusions on a straight line with pitch Y. The average value of the width of the recesses in Structure X and the average value of the width of the protrusions in Structure Y can be measured by observing the cross section in the thickness direction using a digital microscope and measuring it with its length measuring function, or by measuring it with a length measuring tool such as a ruler, the details of which will be described later.
[0048] From the above viewpoint, the average value of the width of the recesses in structure X and the average value of the width of the protrusions in structure Y are preferably 7% or more and 15% or less, more preferably 9% or more and 12% or less. By setting the average value of the width of the recesses in structure X and the average value of the width of the protrusions in structure Y in the above range, high absorption performance can be achieved at the same time as productivity and durability. By setting the average value of the width of the recesses in structure X and the average value of the width of the protrusions in structure Y to 5% or more, the shape of the recesses and protrusions does not become fine, and the reduction in return loss due to the yield during production and damage during use is reduced. In addition, the width of the recesses in structure X and the protrusions in structure Y does not become significantly smaller than the wavelength of the electromagnetic wave, and the effect of improving the return loss in the periodic structure is expected. On the other hand, by setting the average value of the width of the recesses in structure X and the average value of the width of the protrusions in structure Y to 20% or less, the area of the protrusions in structure Y or the recesses in structure X is secured, so the effect of improving the return loss by the uneven structure is increased.
[0049] From the viewpoint of reducing deterioration in performance due to bending or chipping, the laminate sheet of the present invention preferably has at least one of the following features 5 and 6. Feature 5: The depth of the recess in structure X is 70% or less of the sheet thickness and 1% or more of pitch X. Feature 6: The height of the convex portion in structure Y is 70% or less of the sheet thickness and 1% or more of the pitch Y.
[0050] The depth of the recess in Structure X and the height of the protrusion in Structure Y can be measured by observing a cross section in the thickness direction using a digital microscope and measuring it using its length measuring function, or by measuring it with a length measuring tool such as a ruler, and the details of this will be described later.
[0051] The height of the protrusions in Structure Y / the depth of the recesses in Structure X is preferably 50% or less of the sheet thickness, with no particular lower limit being specified, but being 1%. When the height of the protrusions in Structure Y or the depth of the recesses in Structure X is 70% or less of the sheet thickness, it is possible to reduce the deterioration of the electromagnetic wave absorption performance due to bending or chipping of the protrusions.
[0052] Furthermore, the height of the convex portions in structure Y / the depth of the concave portions in structure X is preferably 1% or more of pitch Y / pitch X, and preferably 2% or more, with no upper limit specified, but 100%. When the height of the convex portions in structure Y / the depth of the concave portions in structure X is 1% or more of pitch Y / pitch X, the concave portions and convex portions do not become significantly smaller than the wavelength of the electromagnetic wave, and the effect of improving the return loss in the periodic structure is obtained.
[0053] From the viewpoint of processability, the laminate sheet of the present invention preferably has at least one of the following characteristics 7 and 8. Feature 7: The average thickness of each layer of the alternately laminated unit is 1% or more and 40% or less of the depth of the recess in the structure X. Feature 8: The average thickness of each layer of the alternately laminated unit is 1% or more and 40% or less of the height of the convex portion in structure Y.
[0054] The average thickness of each layer of the alternately laminated unit can be calculated from the thickness of each layer measured by observing a cross section in the thickness direction using a digital microscope and measuring the thickness using its length measuring function. The measurement method will be described in detail later.
[0055] From the above viewpoint, the average thickness of each layer of the alternating laminate unit is preferably 30% or less of the depth of the recess in structure X / height of the protrusion in structure Y, and more preferably 10% or less. The average thickness of each layer of the alternating laminate unit being 40% or less of the depth of the recess in structure X / height of the protrusion in structure Y means that each layer is not excessively thick compared to the protrusion or recess. By adopting such an embodiment, it becomes easy to process the sheet as an integrated material during molding, and a good shape can be obtained. In addition, since the electromagnetic wave absorption performance may decrease if the moldability is poor and a good shape is not obtained, by adopting such an embodiment, the electromagnetic wave absorption performance can also be improved.
[0056] From the viewpoints of electromagnetic wave absorbing performance and design, the laminate sheet of the present invention preferably has at least one of the following features 9 and 10. Feature 9: When the length of pitch X is evaluated at 50 consecutive points in the same direction, the standard deviation is 10% or less of the average value. Feature 10: When the length of pitch Y is evaluated at 50 consecutive points in the same direction, the standard deviation is 10% or less of the average value.
[0057] In order to obtain a stable return loss, it is preferable that the pitch X and pitch Y are stable, and also from the viewpoint of design, it is better that the pitches are uniform. From the above viewpoint, the standard deviation of the pitch X and pitch Y in Features 9 and 10 is preferably 8% or less of the average value. Note that the smaller the standard deviation of the pitch X and pitch Y in Features 9 and 10, the better, so there is no particular limit, but from the viewpoint of feasibility, it is 0.01%.
[0058] To realize features 3 to 10, the pattern and precision of the roll in the case of embossing, or the pattern and precision of the die in the case of imprinting, may be adjusted to the desired shape.
[0059] In the laminated sheet of the present invention, from the viewpoint of increasing the return loss, it is preferable that the thickness of at least one of the outermost layers is 5% or more and 40% or less of the entire sheet. By making the thickness of at least one of the outermost layers 5% or more, it is possible to match the impedance with the atmosphere, suppress surface reflection, and increase the return loss. It is also possible to suppress stacking disorder of the multilayer sheet and increase the return loss. On the other hand, by making the thickness of at least one of the outermost layers 40% or less of the entire sheet, the decrease in the ratio of the stacked structure of the inner layer is suppressed, and the decrease in the return loss in the inner layer is reduced. In order to make the thickness of at least one of the outermost layers 5% or more and 40% or less of the entire sheet, it is effective to adjust the slit width of the lamination device (feed block) described later.
[0060] From the viewpoint of processability and moldability such as embossing, the laminated sheet of the present invention preferably has a maximum Young's modulus at 80°C of 50 MPa or more and 200 MPa or less. From the above viewpoint, it is preferably 70 MPa or more and 170 MPa or less. By making the maximum Young's modulus at 80°C 200 MPa or less, processing such as embossing can be facilitated, and the yield and processing cost can be reduced, and moldability can also be improved. On the other hand, if it is 50 MPa or less, the shape of the film itself may be distorted by the heat generated during molding such as embossing on the surface, and flatness may be deteriorated.
[0061] Young's modulus can be measured by the method described in JIS K-7161 (2014) and JIS K-7127 (1999), the details of which will be described later. The maximum value of Young's modulus at 80 ° C. can be determined by the following procedure. First, Young's modulus at 80 ° C. is measured in an arbitrary direction, and Young's modulus at 80 ° C. in a direction rotated 10 ° clockwise from the measurement direction is measured. Thereafter, the measurement of Young's modulus at 80 ° C. is repeated in the same manner for each 10 ° rotation until the angle with the initial measurement direction becomes 90 ° C. The largest value among the obtained measured values is regarded as the maximum value of Young's modulus at 80 ° C. The same method can be used for the minimum value of Young's modulus at 25 ° C., which will be described later, except that the specified value becomes the minimum value and the measurement temperature is different.
[0062] Examples of methods for adjusting the Young's modulus to fall within this range include a method in which a thermoplastic resin having a glass transition temperature (Tg) of 60 to 90° C. is used in at least one layer (preferably layer B), a method in which molecular chains are oriented in a direction in which the Young's modulus is to be increased by stretching, etc. These methods can be used in combination as appropriate.
[0063] From the viewpoint of strength under room temperature environment, the laminated sheet of the present invention preferably has a minimum Young's modulus at 25°C of 800 MPa or more, more preferably 900 MPa or more. By setting the minimum Young's modulus at 800 MPa or more, the strength at room temperature becomes sufficient and the durability of the uneven shape is improved. There is no particular upper limit, but the feasible range is 10,000 MPa or less.
[0064] Examples of methods for setting the minimum value of Young's modulus at 25° C. within the above range include a method using a high-strength thermoplastic resin, a method of stretching in multiple directions to align molecular chains in the plane, etc. These methods can be used in combination as appropriate.
[0065] The laminate sheet of the present invention preferably has a visible light transmittance of 10% or less, more preferably 7% or less, and even more preferably 1% or less. When used as a building material or equipment housing, depending on the application, deterioration inside the sheet can be suppressed and durability can be improved by making the sheet opaque. In particular, when used outdoors, it is preferable to reduce the light transmittance by adding a pigment or the like to suppress deterioration due to light in the ultraviolet to visible light range.
[0066] The visible light transmittance can be measured by a known spectrophotometer, and the details of the measurement method will be described later. In addition, as a method for making the visible light transmittance of the laminated sheet 10% or less, for example, a method of adding low-transparency particles, pigments, dyes, etc. can be mentioned. In order to reduce the visible light transmittance with a small amount of addition, it is preferable to use carbon-based particles such as carbon nanotubes (CNT), graphite, graphene, and other flat carbons, cylindrical graphite, carbon microcoils, fullerenes, carbon fibers (long fibers, short fibers), acetylene black, channel black, lamp black, thermal black, ketjen black, furnace black, and spherical graphite. In addition, since these carbon materials have electrical conductivity, they also play a role as conductive materials.
[0067] In the laminate sheet of the present invention, the uneven structure may be provided on one side or both sides. When provided on both sides, the uneven shape, pitch, depth, etc. may be the same or different. When provided on both sides, it is also preferable to design the uneven structure to absorb multiple frequency bands by making the uneven structure different on both sides.
[0068] In the laminated sheet of the present invention, it is also preferable to provide a layer that reflects electromagnetic waves (reflective layer) as one of the surface layers or inner layers. By providing a reflective layer, the laminated sheet is provided with a reflecting performance in addition to an absorbing performance of electromagnetic waves, so that the electromagnetic wave shielding property of the laminated sheet can be enhanced. To provide the reflective layer, a coating layer containing a material exhibiting suitable electrical conductivity / magnetic properties may be applied, or a different resin layer / mesh layer may be laminated via an adhesive sheet or the like. Here, examples of the "material exhibiting electrical conductivity / magnetic properties" include carbon nanotubes (CNTs), flat carbon such as graphite, graphite, and graphene, cylindrical graphite, carbon microcoils, fullerenes, carbon fibers (long fibers, short fibers), acetylene black, channel black, lamp black, thermal black, Ketjen black, furnace black, and carbon particles such as spherical graphite. From the viewpoint of dispersibility, CNTs, thermal black, and Ketjen black are particularly preferable. In addition, resin / metal layers can be laminated appropriately according to the required function using techniques such as sputtering (such as planar or rotary magnetron sputtering), evaporation (such as electron beam evaporation), chemical vapor deposition, metal-organic chemical vapor deposition, plasma-enhanced / assisted / activated chemical vapor deposition, and ion sputtering, which are used to coat sheets with metals or the like.
[0069] Hereinafter, the method for producing a laminate sheet of the present invention will be described with reference to specific examples, but the present invention is not limited to the following embodiments.
[0070] First, a laminated sheet in which rubber or a thermoplastic elastomer is used as a base polymer of a substrate will be described as an example. First, a predetermined amount of desired particles (for example, conductive material, etc.) is mixed with the base polymer, and kneaded and contained in a known device such as a kneader, a Banbury mixer, a mill mixer, a roll mill, a jet mill, or a ball mill to obtain a particle-containing base polymer mixture. The base polymer alone or the prepared particle-containing base polymer is rolled or melt extruded by a batch press to form a sheet of a desired thickness to obtain a sheet corresponding to layer A and a sheet corresponding to layer B. Then, the prepared sheets corresponding to layer A and layer B (preferably containing particles) are alternately stacked in a total of 5 layers or more, and pressed or laminated to obtain a laminated sheet. The fusion temperature at this time depends on the type of polymer to be used, but is preferably 150 to 400°C, more preferably 250 to 380°C.
[0071] Next, a manufacturing method of a laminated sheet using a thermoplastic resin, which is one of the preferred embodiments of the present invention, in which only the B layer contains particles (conductive material, etc.) and the A layer does not contain particles, will be described as an example. First, the thermoplastic resin prepared in the form of pellets and a predetermined amount of particles are melt-kneaded at 250 to 300 ° C. by a twin-screw extruder and extruded into a gut shape, which is cooled in a water tank and cut with a chip cutter to prepare a master pellet containing particles. At this time, the particles may be dry-blended with the resin and then metered and fed from a hopper, or side-fed into the molten resin from an arbitrary position of the extruder using a side feeder. The feeding method is not limited to the above, and can be appropriately selected according to the specific gravity and shape of the particles used.
[0072] The thermoplastic resin compositions constituting the layers A and B are then dried in hot air or under vacuum, and fed to separate extruders, where they are heated and melted to a temperature equal to or higher than the melting point of the thermoplastic resin. The extrusion rate is then made uniform using a gear pump or the like, and the thermoplastic resin composition is discharged, and foreign matter, modified thermoplastic resin, and the like are removed using a filter or the like.
[0073] Next, these thermoplastic resin compositions are laminated in a multi-layer lamination device capable of laminating the desired number of layers, molded into a desired shape with a die, and discharged into a sheet. The sheet-like material discharged from the die is extruded onto a cooling body such as a casting drum, and cooled and solidified to become a cast sheet. At this time, since the cast sheet itself exhibits electrical conductivity, it is preferable to use a method in which air is blown out from a slit-shaped, spot-shaped, or planar device to bring the cast sheet into close contact with a cooling body such as a casting drum and rapidly solidify it, or a method in which the cast sheet is brought into close contact with a cooling body with a nip roll and rapidly solidify it. At this time, the temperature of the casting drum is preferably 20 to 40°C.
[0074] As the multi-layer lamination device, a multi-manifold die, a feed block, a static mixer, etc. can be used, but in particular, in order to efficiently obtain the multi-layer laminate of the present invention, it is preferable to use a feed block having a fine slit. When such a feed block is used, the device does not become extremely large, so the amount of foreign matter generated due to thermal deterioration is small, and high-precision lamination is possible even when the number of layers is extremely large. In addition, the lamination precision in the width direction is also significantly improved compared to the conventional technology. Furthermore, this device has the advantages that the thickness of each layer can be adjusted by the shape (length, width) of the slit, making it easy to achieve an arbitrary layer thickness, and that the effect of the resin flow during the lamination process makes it easy to orient the particles in the direction of the laminated sheet surface. In addition, from the viewpoint of suppressing lamination disturbance, it is preferable that the lamination ratio of the thermoplastic resin composition constituting the A layer and the B layer is A:B=1:0.5 to 1:2.
[0075] When a laminate sheet is produced using a slit-type feedblock, the thickness and distribution of each layer can be adjusted by adjusting the pressure balance by changing the length and width of the slit. The length of the slit refers to the length of the comb teeth that form the flow path for alternately flowing layers A and B inside the slit plate. In addition, a method of forming a laminate in the feedblock and then stacking the layers through a static mixer to double the number of layers can also be used to increase the number of layers.
[0076] The obtained cast sheet can be biaxially stretched in the longitudinal direction and the width direction as necessary. When biaxial stretching is performed, the stretching may be performed sequentially or simultaneously. If necessary, re-stretching may be performed in the longitudinal direction and / or the width direction. The longitudinal direction refers to the direction in which the sheet runs during the production process (the winding direction when the sheet is wound into a roll), and the width direction refers to the direction perpendicular to the longitudinal direction within the plane of the sheet.
[0077] First, sequential biaxial stretching in which the sheet is stretched in the longitudinal direction and then in the transverse direction will be described. Here, stretching in the longitudinal direction refers to uniaxial stretching for giving the sheet a molecular orientation in the longitudinal direction, and is usually performed by the difference in peripheral speed of the rolls. This stretching may be performed in one stage, or in multiple stages using a plurality of pairs of rolls. The stretching ratio varies depending on the type of resin, but is usually preferably 1.1 to 7.0 times, and particularly preferably 1.5 to 4.0 times. In addition, it is preferable to set the stretching temperature within the range of the glass transition temperature to the glass transition temperature + 100 ° C. and below the melting point for all the thermoplastic resins constituting the sheet. The uniaxially stretched laminate sheet thus obtained can be subjected to surface treatment such as corona treatment, frame treatment, and plasma treatment as necessary, and then a primer layer can be formed to improve adhesion with the film to be laminated on the upper side. In the in-line coating process, the primer layer may be applied to one side, or to both sides simultaneously or one side at a time.
[0078] The stretching in the width direction means stretching for giving a width direction orientation to the sheet, and is usually performed by conveying the sheet while holding both ends in the width direction with clips using a tenter. The stretching ratio varies depending on the type of resin, but is usually preferably 1.1 to 7.0 times, and particularly preferably 1.5 to 5.0 times. The stretching process can suppress the variation in attenuation and suppress the decrease in electromagnetic wave attenuation after molding. In addition, the stretching temperature is preferably within the range of glass transition temperature to glass transition temperature + 120 ° C for all thermoplastic resins constituting the A layer and B layer of the sheet. The laminated sheet thus biaxially stretched is subjected to heat treatment at a temperature higher than the stretching temperature and lower than the melting point in the tenter, and is uniformly cooled slowly, and then cooled to room temperature and wound up. In addition, if necessary, a relaxation treatment or the like may be used in the longitudinal direction and / or width direction when slowly cooling from the heat treatment in order to impart a low orientation angle and thermal dimensional stability to the sheet.
[0079] Next, the case of simultaneous biaxial stretching will be described. In the case of simultaneous biaxial stretching, the obtained cast sheet may be subjected to surface treatment such as corona treatment, frame treatment, plasma treatment, etc., as necessary, and then functions such as easy slip, easy adhesion, and antistatic properties may be imparted by in-line coating. In the in-line coating process, the coating layer may be applied to one side of the sheet, or may be applied to both sides simultaneously or one side at a time.
[0080] Next, the cast sheet is introduced into a simultaneous biaxial tenter, and conveyed while holding both ends of the sheet in the width direction with clips, and is stretched in the longitudinal direction and the width direction simultaneously and / or stepwise. The simultaneous biaxial stretching machine (tenter) may be of the pantograph type, screw type, drive motor type, linear motor type, etc., but the drive motor type or linear motor type, which can change the stretching ratio arbitrarily and can perform relaxation treatment at any location, is preferable. The stretching ratio varies depending on the type of resin, but usually, the area ratio is preferably 2.0 to 50 times, and more preferably 4.0 to 20 times. The stretching speed may be the same speed, or may be different speeds in the longitudinal direction and the width direction. The stretching temperature is preferably within a range of the glass transition temperature to the glass transition temperature + 120°C for all resins constituting the alternating laminate unit (A layer, B layer).
[0081] In order to impart planarity and dimensional stability to the sheet thus simultaneously biaxially stretched, it is preferable to subsequently perform heat treatment in a tenter at a temperature equal to or higher than the stretching temperature and equal to or lower than the melting point of all the resins constituting the sheet. During this heat treatment, in order to suppress the distribution of the main orientation axis in the width direction, it is preferable to perform a relaxation treatment in the longitudinal direction immediately before and / or immediately after entering the heat treatment zone. After being heat treated in this manner, the sheet is uniformly cooled slowly, cooled to room temperature, and wound up. In addition, if necessary, a relaxation treatment in the longitudinal direction and / or width direction may be performed when slowly cooling from the heat treatment. A relaxation treatment in the longitudinal direction may also be performed immediately before and / or immediately after entering the heat treatment zone.
[0082] Next, a product using the laminated sheet of the present invention will be described. The laminated sheet of the present invention can be used well as a building material due to its excellent formability and strength. That is, the building material of the present invention has the laminated sheet of the present invention. Here, the building material refers to materials used in buildings in general. The building material of the present invention can be used for the inner walls of buildings that perform 5G communication, such as offices and smart factories, to suppress unnecessary reflection of radio waves indoors and reduce radio interference caused by interference and resonance. In particular, since it has wide-band absorption, it is effective when the incident light is oblique or when the communication band is wide. The building material of the present invention can also be used for movable separations, doors, screens, etc. other than built-in walls.
[0083] The laminated sheet of the present invention can also be used well as a communication device housing. That is, the communication device housing of the present invention has the laminated sheet of the present invention. Here, the communication device housing refers to the housing of a device that communicates by transmitting, receiving, or transmitting and receiving electromagnetic waves. Since the laminated sheet of the present invention has excellent formability, it can be arranged as a housing without impairing the design of the communication device, and since it has wideband absorption, it can exert a certain electromagnetic wave absorption effect even in an area where the electric field distribution near the antenna is irregular. A preferred embodiment of the communication device housing of the present invention is, for example, an embodiment in which the laminated sheet of the present invention is installed in the direction opposite to the transmitting or receiving direction of at least one of the receiving antenna, the transmitting antenna, and the transmitting and receiving antenna. By adopting such an embodiment, the laminated sheet of the present invention is present behind the antenna where the back lobe is maximized, and the maximum communication failure suppression effect can be obtained with a small ground surface area. It is also preferable to additionally install it on the side of the antenna to absorb the side lobe.
[0084] The distance between the laminated sheet and the antenna is preferably at least one time the wavelength of the electromagnetic waves to be transmitted or received. If the distance to the antenna is too close, it may hinder heat dissipation or have a negative effect on the main lobe. There is no upper limit on the distance, but from the perspective of miniaturizing communication devices and the fact that if the distance is too far, the required area becomes large and costs increase, the upper limit is set to 1,000 times the wavelength of the electromagnetic waves to be transmitted or received.
[0085] In particular, in the case of communication devices that use linearly polarized waves, it is preferable that the polarization direction of the antenna's main lobe and the direction in which the laminate sheet has strong electromagnetic wave absorption are perpendicular to each other. In this manner, components other than the main lobe are preferentially absorbed, so that unnecessary electromagnetic waves can be absorbed without affecting communication.
[0086] In addition, the laminated sheet of the present invention or the housing for communications devices of the present invention can be mounted on various devices for the purposes of preventing false images caused by electromagnetic waves used in 4G / 5G communications, wireless LAN, and collision prevention (ITS) radar, reducing radiation of unnecessary electromagnetic waves from electronic devices, semiconductors, and circuits installed inside the housings of computers, mobile phones, radios, measuring instruments, medical devices, vehicle bumpers, and the like, and preventing malfunctions of devices due to radiation from external or adjacent devices.
[0087] Further, preferred applications of the laminate sheet of the present invention include transportation means such as vehicles, aircraft, ships, etc. (whether manned or unmanned) having the laminate sheet of the present invention, walls of structures such as buildings, tunnels, guardrails, highways, bridges, and steel towers, and communication facilities such as telegraph and telephone facilities.
[0088] The laminated sheet of the present invention can be applied by attaching it to structures such as floors, ceilings, walls, windows, and pillars directly via an adhesive or via other sheets, shielding plates, panels, etc. It can also be used as a wall or window material for a shielded room to prevent the effects of external electromagnetic jamming noise. EXAMPLES
[0089] The present invention will be described below with reference to examples, but the present invention is not limited to these examples.
[0090] (Methods for measuring characteristics and evaluating effects) The methods for measuring the characteristics and evaluating the effects of the present invention are as follows.
[0091] (1) Return loss (S 11 ), frequency bandwidth, peak frequency For each measurement frequency, the measurement unit and measurement method were changed as follows to obtain a return loss curve for the laminate sheet.
[0092] (1-1) Frequency band between 1 GHz and 40 GHz A vector network analyzer (E8361A) manufactured by Agilent Technologies was used. A donut-shaped coaxial waveguide with an outer diameter of φ7 mm and an inner diameter of φ3.04 mm was used for the 0.5 GHz to 18 GHz frequency band, a rectangular waveguide with a rectangular shape of 4.32 mm × 10.67 mm was used for the 18 to 26.5 GHz frequency band, and a rectangular waveguide with an inner shape of 3.56 mm × 7.11 mm was used for the 26.5 to 40 GHz frequency band. A sample of the laminated sheet was punched out and inserted vertically into each of the above-mentioned waveguides for measurement. The measurement interval was set so that 200 points could be measured for each frequency band. A 3 mm aluminum metal plate was placed on the back of the laminated sheet sample, and the incident electromagnetic wave was totally reflected when there was no electromagnetic wave absorption by the laminated sheet. S, which represents the intensity ratio of the reflected electromagnetic wave to the incident electromagnetic wave, 11 is taken as the return loss, and a return loss curve (a curve with return loss on the vertical axis and frequency band on the horizontal axis) is obtained.
[0093] (1-2) Frequency band between 40 GHz and 110 GHz A measurement sample was prepared by attaching an aluminum metal plate to the back of a 150mm square laminated sheet. Using a lens antenna type oblique incidence type electromagnetic wave absorber (electromagnetic wave absorbing material) return loss measurement device LAF-26.5B manufactured by Keycom Co., Ltd., electromagnetic waves were irradiated at an oblique incidence of 15° in accordance with JIS R 1679 (2007), and the return loss was measured for each frequency band of 33 to 50 GHz (WR-22), 50 to 75 GHz (WR-15), and 75 to 110 GHz (WR-10), and a return loss curve was obtained.
[0094] (1-3) Frequency band exceeding 110 GHz and up to 1000 GHz The terahertz laser used was an RM9-THz (Ophir Optronics Solutions, 0.11-30 THz), and the detector was a TeraPyro (Japan Laser, 0.11-30 THz). Before measuring the sample, a 3 mm aluminum metal plate was placed to measure the electromagnetic waves reflected at an incident angle of 15°. 11 After calibrating to 0 dB, a 30 mm square sample was placed in front of an aluminum metal plate and measurements were performed. Measurements were performed by directing electromagnetic waves emitted from a terahertz laser of each frequency onto the sample at an incident angle of 15 degrees and analyzing the intensity of the reflected laser light. The reflection intensity was divided by the incident light intensity, and the logarithm with base 10 was taken as the return loss to obtain a return loss curve.
[0095] The return loss curves obtained in (1-1), (1-2), and (1-3) above were analyzed, and the return loss at the maximum peak, the frequency at that time (peak frequency), the width of the frequency band including the peak frequency and showing a return loss of 5.0 dB or more (frequency bandwidth of 5 dB or more), and the width of the frequency band including the peak frequency and showing a return loss of 20.0 dB or more (frequency bandwidth of 20 dB or more) were identified and calculated.
[0096] (2) Layer thickness, number of layers, layer configuration, uneven structure The layer thickness, number of layers, stacking configuration, and uneven structure of the laminated sheet were obtained by observing the cross section of a sample cut parallel to the thickness direction using a microtome with a microscope. More specifically, a digital microscope VHX5000 (manufactured by Keyence Corporation) was used to observe the cross section of the laminated sheet at a magnification of 100 to 5000, and a cross-sectional photograph was taken to identify the number of layers, stacking configuration, and uneven structure, and the thickness of each layer, the pitch, width, and depth / height of the unevenness were measured using the length measurement function of the microscope. For uneven structures of 5 mm or more, the cross section or surface was photographed with a digital camera DSC-HX60V (manufactured by SONY Corporation) together with a ruler, and the image was imported into ImageJ and analyzed to calculate. Note that the cross section parallel to the thickness direction was obtained so as to pass through the center of the concave or convex parts so that the pitch could be measured.
[0097] (3) Young’s modulus The sample was cut into a rectangular shape of 1 cm x 20 cm (measurement direction), and the Young's modulus was measured when the sample was pulled at 23 ° C or 80 ° C, 5 cm between the chucks, and 300 mm / min using an automatic film strength and elongation measuring device "Tensilon" (registered trademark) AMF / RTA-100 manufactured by Orientec Co., Ltd. The Young's modulus was measured by the method described in JIS K-7161 (2014) and JIS K-7127 (1999). The maximum Young's modulus at 80 ° C was determined by the following procedure. First, the Young's modulus at 80 ° C was measured in an arbitrary direction, and the Young's modulus at 80 ° C in a direction rotated 10 ° clockwise from the measurement direction was measured. Thereafter, the measurement of the Young's modulus at 80 ° C was repeated in the same manner every time it was rotated 10 ° until the angle with the initial measurement direction became 90 °. The largest value among the measured values obtained was taken as the maximum Young's modulus at 80 ° C. The minimum value of Young's modulus at 25° C. was also determined using a similar method, except that the specific value was the minimum value and the measurement temperature was different.
[0098] (4)Visible light transmittance A Hitachi U-4100 spectrophotometer was used. An integrating sphere was attached, and the average relative transmittance from 400 nm to 800 nm was measured, assuming the transmitted light measured using the reflected light of an aluminum oxide standard white plate (included with the unit) to be 100%, and this was taken as the visible light transmittance.
[0099] (5) False positive prevention A 15cm square metal plate was placed 1m in front of the millimeter wave radar TitanT18PE_01030103_2R5D (manufactured by Estacaya). When no sample was placed, false detections occurred due to reflections from the metal parts of the millimeter wave radar and the floor. The metal parts of the millimeter wave radar and the floor were covered with samples, and the following judgments were made based on the level of false detection suppression. Levels A to C are practical levels. A: False positive signals were suppressed by more than 15 dB. B: False positive signals were suppressed by 10 dB or more but less than 15 dB. C: False positive signals were suppressed by 5 dB or more but less than 10 dB. D: False positive signal suppression was less than 5 dB.
[0100] (6) Increase communication strength A 15cm square metal plate was placed 1m in front of the millimeter wave radar TitanT18PE_01030103_2R5D (manufactured by Estacaya). In addition, a metal case as shown in Figure 6 was placed 3cm behind the millimeter wave radar. The metal parts of the millimeter wave radar and the floor were covered with the sample. At this time, the detection strength of the metal plate decreased due to reflection from the metal on the inner surface of the metal case. The level at which the detection strength improved by covering the inner surface of the metal case with the sample was judged as follows. Levels A to C are practical levels. A: The detection signal has improved by more than 6dB. B: The detection signal improved by more than 4 dB but less than 6 dB. C: The detection signal improved by more than 2 dB but less than 4 dB. D: The improvement in the detection signal was less than 2 dB.
[0101] (7) Communication stability Using the same configuration as in the evaluation in (6), the detection intensity was recorded every second, and 3600 points were evaluated in succession to record the fluctuations. The standard deviation of the detection intensity at 3600 points was calculated, and the following judgments were made based on the value. A: The fluctuation (standard deviation) was between 0 dB and 2 dB. B: The fluctuation (standard deviation) exceeded 2 dB.
[0102] (8) Formability Molding was performed under the following conditions using a vacuum molding machine (Seiko Sangyo Co., Ltd. 300X). Heating was performed using an infrared heater, and the temperature was determined by attaching a heat label to the sample. Molding tests were performed three times for each sample. The appearance after molding was visually inspected and the following evaluations were performed. A to C can be used in applications requiring molding, and C can be used in applications that do not require molding. Heating time: 60 seconds Heating temperature: 110℃ Vacuum pump pressure: 0.17MPa Moulded shape: box shape, 5cm wide, 7.5cm long and 2cm deep. A: All samples were in good contact with the edges and corners and were wrinkle-free. B: One sample had small spaces around the edges or vertices, but two samples were tightly sealed around the edges and vertices and were wrinkle-free. C: One or two samples had air pockets around the edges and corners, causing wrinkles, or two samples had small spaces around the edges or corners, but one sample was sealed around the edges and corners and had no wrinkles. D: All three samples had spaces around the edges or air pockets near the vertices, causing wrinkles.
[0103] (9) Strength The box formed in (8) was dropped 10 times from a height of 1.5 m onto a metal plate, and the presence or absence of cracks was confirmed. A can be used in applications requiring strength, B can be used in applications requiring strength but is inferior to A, and C can only be used in applications not requiring strength. A: No cracks were observed at all. B: One crack less than 5 mm in size was observed. C: Two or more cracks or cracks exceeding 5 mm were observed.
[0104] (10) Surface roughness (Ra) If the depth and pitch of the irregularities were 0.1 mm or less, they were evaluated using a 3D roughness meter, and if either exceeded 0.1 mm, they were evaluated using a 3D shape measuring device.
[0105] (10-1) Surface roughness (0.1 mm or less) The surface morphology of the release film was measured using a three-dimensional microscopic shape measuring instrument (model ET-4000A, manufactured by Kosaka Laboratory Co., Ltd.) under the following measurement conditions.
[0106] (Measurement conditions) Measuring device: 3D micro shape measuring instrument (model ET-4000A) manufactured by Kosaka Laboratory Co., Ltd. Stylus: Model ET-1480 (tip radius 0.5μmR, diameter 2μm, made of diamond) ·Stylus pressure: 100μN X-axis measuring length: 1.0mm -Y axis measurement length: 1.0mm ·Measurement speed: 0.1mm / sec X-axis feed pitch: 1μm (measurement interval) -Y-axis feed pitch: 5μm (measurement interval) Number of Y-axis lines: 81 (number of measurements) Z-axis measurement magnification: 10,000x (vertical magnification) Retraction amount: 2mm Next, the obtained measurement data was imported into a 3D surface roughness analysis system (model TDA-31), and the center surface average roughness Ra, a 3D parameter defined in the manual that came with the measuring instrument and analysis system and conforming to JIS-B0601 (2013), was calculated under the following analysis conditions. Note that the above measurement was performed by taking an arbitrary direction as the X-axis and another measurement perpendicular to that direction as the X-axis, and the average value of two measurements was used.
[0107] (10-2) Surface roughness (over 0.1 mm) The surface of the sample was captured by a laser microscope VK-X3000 manufactured by Keyence Corporation at 20 times magnification with the measurement mode set to laser confocal to obtain multiple images. Then, 25 of the images were linked using an image linking application (version 3.3.1.0) attached to the laser microscope, and further image processing was performed. Image processing was performed using a multi-file analysis application (version 3.2.0.66) attached to the microscope. The image processing in the multi-file analysis application was performed in the following order from (1) to (5) using an image processing tool. (1) Height cut level of the image processing tool: Medium, (2) Surface shape correction of the same tool: Waviness removal correction strength 5, (3) Surface shape correction of the same tool: Waviness removal correction strength 5, (4) Reference surface setting of the same tool: Area specified continuous surface extraction, (5) Calculation of surface roughness (Ra) of the entire area.
[0108] (11) Glass transition temperature Tg, melting point According to JIS K-7122 (1987), 3.0 mg of the film was weighed out, and a differential scanning calorimeter (EXSTAR DSC6220 manufactured by Seiko Instruments) was used to heat the resin from 25°C to Tmax [°C] at a heating rate of 20°C / min to obtain a differential scanning calorimeter chart. Tmax [°C] was set to 300°C. From the obtained differential scanning calorimeter chart, the melting peak temperature was determined based on the method described in JIS K-7121 (1987). The highest melting peak temperature among the obtained melting peak temperatures was taken as the melting point of the film. For Tg, the highest intermediate glass transition temperature among the intermediate glass transition temperatures determined based on the method described in JIS K-7121 (1987) was used.
[0109] (Resins, etc. used in manufacturing) Resin 1: Polyethylene terephthalate with IV (intrinsic viscosity, unit dl / g) 0.78, Tg 75°C, and melting point 255°C Resin 2: Polyethylene terephthalate copolymerized with 25 mol% spiroglycol based on the total diol component and 30 mol% cyclohexanedicarboxylic acid based on the total dicarboxylic acid component (PET / SPG / CHDC) (IV: 0.72, Tg: 80°C, melting point: 250°C) Resin 3: Polyethylene terephthalate with IV 0.62, Tg 80°C, melting point 255°C Conductive particle 1: Carbon black (spherical carbon, primary particle diameter 40 nm, DBP oil absorption 360) Conductive particle 2: Indium tin oxide (primary particle diameter 30 nm) Metal particle 1: Flat iron (average particle size 1.6 μm, aspect ratio 0.5) Metal particle 2: Carbonyl iron (average particle size 3.6 μm, aspect ratio 1.0) Example 1 70 parts by mass of resin 1 was mixed with 20 parts by mass of resin 2, and 10 parts by mass of conductive particles 1 were fed by side feed and kneaded in a twin-screw extruder to prepare a conductive master pellet. Resin 1 was used on the A layer side, and the conductive master pellet was used on the B layer side. The prepared polyethylene terephthalate resin and conductive master pellet were each fed into a twin-screw extruder, and melt-kneaded at 280°C in each twin-screw extruder. The kneading conditions in each twin-screw extruder were a screw rotation speed of 0.7 relative to the discharge amount. Next, the extruded resin and resin mixture were merged in five multi-manifold type feed blocks at a lamination ratio of 1.0 (1:1), and five layers were laminated alternately in the thickness direction. Next, the mixture was fed into a T-die and formed into a sheet, and then quenched and solidified on a casting drum kept at a surface temperature of 25°C to form an alternating laminate unit with a thickness of 0.5 mm. At this time, the layers were laminated so that the A layer was located on the outermost surface on both sides. The obtained alternate laminated unit was preheated with a roll at 85°C, and a continuous groove was formed on one side with an embossing roll (temperature 85°C) that had grooves 100μm deep, 1mm wide, and 5mm pitch parallel to the longitudinal direction, to produce a laminated sheet. The embossing roll was made of hard chrome plated material, and the opposing roll was a hard chrome plated roll with a false surface finish. The sample width was 200mm, and the embossing process was performed with a pressing pressure of 1t and a conveying speed of 2m / min. The evaluation results are shown in Tables 1 and 2.
[0110] (Examples 2 to 45, Comparative Examples 1 and 2) As shown in Table 1, laminated sheets were produced in the same manner as in Example 1, except that the uneven structure, composition of each layer, total thickness, number of layers, thickness of each layer, and uneven shape (pitch, peripheral width (average width of uneven / protruding parts), depth / height) were changed. The evaluation results are shown in Tables 1 and 2. The total thickness was adjusted by changing the casting speed, the number of layers and the thickness of each layer by changing the number of layers in the feed block and the width of each slit, and the uneven structure and uneven shape by changing the shape of the embossing roll.
[0111] Comparative Example 3 Except for not carrying out the embossing treatment, a laminate sheet was produced in the same manner as in Example 1. The evaluation results are shown in Tables 1 and 2.
[0112] [Table 1]
[0113] [Table 2] [Industrial Applicability]
[0114] According to the present invention, it is possible to provide a laminate sheet that is excellent in formability, strength, and electromagnetic wave absorption properties, and is capable of absorbing electromagnetic waves over a wide frequency range due to its uneven structure. Since the laminate sheet of the present invention has the above properties, it can be suitably used as a building material or a housing for communication devices. [Explanation of symbols]
[0115] 1 Recess 2 Convex 3 Pitch
Claims
1. A laminated sheet characterized in that the return loss at the maximum peak in a return loss curve in a frequency band of 1 GHz to 1000 GHz is 5.0 dB or more, the laminated sheet includes an alternating laminate unit in which two different types of layers (layers A and layers B) are alternately laminated to a total of five or more layers, and the laminated sheet has an uneven structure.
2. 2. The laminate sheet according to claim 1, wherein when a structure in which a convex portion is surrounded by a concave portion is defined as structure X and a structure in which a concave portion is surrounded by a convex portion is defined as structure Y, the concave-convex structure has at least one of structure X and structure Y.
3. The laminated sheet according to claim 2, having at least one of the following characteristics 1 and 2. Feature 1: In the structure X, the distance between the centers of the most adjacent convex portions (pitch X) is constant. Feature 2: The distance (pitch Y) between the centers of the most adjacent recesses in the structure Y is constant.
4. 4. The laminated sheet according to claim 3, wherein at least one of the pitch X and the pitch Y is 0.6 mm or more and 30 cm or less.
5. The laminated sheet according to claim 3, having at least one of the following characteristics 3 and 4. Feature 3: The average width of the recesses in the structure X is 5% to 20% of the pitch X. Feature 4: The average width of the convex portion in the structure Y is 5% or more and 20% or less of the pitch Y.
6. The laminated sheet according to claim 3, having at least one of the following characteristics 5 and 6. Feature 5: The depth of the recess in the structure X is 70% or less of the sheet thickness and 1% or more of the pitch X. Feature 6: The height of the convex portion in the structure Y is 70% or less of the sheet thickness and 1% or more of the pitch Y.
7. The laminated sheet according to claim 2, having at least one of the following characteristics 7 and 8. Feature 7: the average value of the thickness of each layer of the alternating laminate unit is 1% to 40% of the depth of the recess in the structure X. Feature 8: the average value of the thickness of each layer of the alternating laminate unit is 1% or more and 40% or less of the height of the convex portion in the structure Y.
8. The laminated sheet according to claim 3, having at least one of the following features 9 and 10. Feature 9: When the length of the pitch X is continuously evaluated at 50 points in the same direction, the standard deviation is 10% or less of the average value. Feature 10: When the length of the pitch Y is continuously evaluated at 50 points in the same direction, the standard deviation is 10% or less of the average value.
9. 2. The laminate sheet according to claim 1, wherein the thickness of at least one outermost layer is from 5% to 40% of the entire sheet.
10. 2. The laminate sheet according to claim 1, wherein the maximum value of Young's modulus at 80° C. is 50 MPa or more and 200 MPa or less.
11. 2. The laminate sheet according to claim 1, having a minimum Young's modulus at 25°C of 800 MPa or more.
12. 2. The laminate sheet according to claim 1, which has a visible light transmittance of 10% or less.
13. 2. The laminate sheet according to claim 1, wherein the frequency bandwidth in which the return loss is 5.0 dB or more at the maximum peak is 1.0 GHz or more and 100 GHz or less.
14. 2. The laminate sheet according to claim 1, wherein the frequency bandwidth in which the return loss is 20 dB or more at the maximum peak is 1.0 GHz or more and 20 GHz or less.
15. A building material comprising the laminate sheet according to any one of claims 1 to 14.
16. A housing for a communication device, comprising the laminate sheet according to any one of claims 1 to 14.
17. The housing for a communication device according to claim 16, which has a laminate sheet according to any one of claims 1 to 14 in a direction opposite to the direction of transmission or reception of at least one of a receiving antenna, a transmitting antenna, or a transmitting / receiving antenna, and the distance between the laminate sheet and the antenna is 1 to 1000 times the wavelength of the electromagnetic wave to be transmitted or received.
18. 17. The communications device housing according to claim 16, wherein the polarization direction of the main lobe of the antenna and the direction in which the laminate sheet exhibits strong electromagnetic wave absorption are perpendicular to each other.
Citation Information
Patent Citations
Electromagnetic wave absorbing material
JP2003158395A
Multilayer optical bandpass film with electromagnetic interference shielding for optical display filters
JP2011502285A
Electromagnetic wave absorbing material
JP2017118073A
Electromagnetic wave absorber
JP2019057730A
Electromagnetic wave absorber
JP2019102665A